The lives of objects: material culture, experience, and the real in the history of early Christianity - Kotrosits, Maia ca. 20./21. Jh. (Class 200: new studies in religion, 2020)
Objects made real: the art of description -- Citizens of fallen cities: ruins, diaspora, and the material unconscious -- Histories unwritten in stone: the frustrations of memorialization -- Tertullian of Carthage and the materiality of power (with Carly Daniel-Hughes) -- The perils of translation: martyrs' last words and the cultural materiality of speech -- Penetration and its discontents: agency, touch, and objects of desire -- Darkening the discipline: fantasies of efficacy and the art of redescription.